Kesiapan Guru dalam Mengimplementasikan Kurikulum Merdeka - Samuel Ben Gurion (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
The progress of a nation is influenced by education. The curriculum is a factor that has a very big influence on educational development. In the Merdeka Curriculum currently implemented, teachers need to adjust teaching preparation, evaluation techniques, and activities carried out in the learning process at school. Module creation, differentiated learning, and the Pancasila Student Profile Development Project are some of them. This research aims to determine the extent of teacher readiness in implementing the Merdeka Curriculum. The research method uses descriptive analysis techniques with a literature review. The research results show that teachers are not fully ready to face curriculum changes. This can be seen from the fact that teachers still need to understand curriculum paradigms that are different from before and learning methods that have also changed. To overcome this, good cooperation and communication are needed between the school, parents, and the government so that this curriculum can run according to objectives.